Innovation in China challenging the global science and technology system - Appelbaum, Richard P.; Cao, Cong; Han, Xueying; Parker, Rachel; Simon, Denis (China today, 2018)
China is in the midst of transitioning from a manufacturing-based economy to one driven by innovation and knowledge. In this up-to-date investigation, leading experts evaluate China's state-led approach to science and technology and provide a comprehensive analysis of which policies have contributed to its successes and failures, and its future.